Ethical and methodological challenges in research with hard-to-reach groups: examples from research on family caregivers for migrant older adults living with dementia - Tezcan-Güntekin, Hürrem; Özer-Erdogdu, Ilknur; Yilmaz-Aslan, Yüce; Aksakal, Tugba; Bird, Rona (Alice Salomon Hochschule Berlin, 2021)
Family caregivers of migrants with dementia constitute a population group that is hard to reach for research participation due to factors such as shame about the disease and past experiences of discrimination. In this article, research-ethical challenges associated with participant recruitment and qualitative data collection among relatives of migrants with dementia are discussed. Over a period of 8 years, 3 studies were conducted to investigate the experiences of family caregivers for persons with dementia of Turkish descent in Germany. Across these studies, a total of 32 family caregivers were interviewed. In this article, based on the "Principles of Biomedical Ethics" according to Beauchamp and Childress (2009), research-ethical conflicts associated with sampling methods and the presence of third parties during qualitative interviews are discussed. The potential risks emanating from sampling strategies and the presence of third parties during interviews regarding the voluntary nature of study participation are examined. Additionally, this article formulates recommendations for ensuring truly voluntary participation and protecting both the participants (family caregivers) and relatives with dementia from harm. These practical recommendations aim to help future researchers to avoid ethical pitfalls and represent a roadmap for making necessary methodological decisions. Quelle: AliceOpen.
Veröffentlicht auf aliceOpen, dem Publikationsserver der Alice Salomon Hochschule Berlin am 19.01.2022
Keywords: Einwanderer; Demenz; Deutschland